Characterization of commercial common wheat cultivars for resistance to tan spot causative agent - N. M. Kovalenko; E. L. Shaydayuk; E. I. Gultyaeva (Биотехнология и селекция растений, 2022)
Tan spot of wheat (pyrenophorosis) is a worldwide spread and economically significant disease of wheat. Growing resistant cultivars is an environmentally friendly method of disease control. The aim of the present work was to assess tan spot resistance in common wheat cultivars recommended for cultivation in the Russian Federation, and to identify the dominant Tsn1 allele using a molecular marker. The assessment involved 39 winter and 31 spring wheat cultivars included in the State Register of Selection Achievement in 2018-2020. Evaluation of wheat resistance was carried out in laboratory conditions under artificial inoculation of seedlings and leaf segments. Two isolates of Pyrenophora tritici-repentis (Died.) Drechs, producing ToxA toxin (I_ToxA) and ToxB toxin (ToxB) were used. The dominant allele of the Tsn1 gene was identified using the Xfcp623 marker. A high level of resistance (R) to both isolates (I_ToxA and I_ToxB) was shown by spring cultivars ‘Grenada’ and ‘Silach’; moderate resistance (MR) was demonstrated by winter cultivars ‘Felicia’ and ‘Akhmat’ and spring cultivars ‘Omskaya 42’, ‘Zauralskaya Zhemchuzhina’, ‘Radmira’, ‘Tarskaya 12’ and ‘Extra’. A resistant reaction (R, MR) to the isolate I_ToxA was typical for 26% of winter cultivars and 45% of spring ones. The number of cultivars resistant to the I_ToxB isolate was significantly higher (59% and 52%, respectively). The total fraction of cultivars resistant to the isolate I_ToxA (reaction R, MR) in the collection of winter wheat was 26% and 45% in the spring wheat collection; while the fractions of cultivars resistant to the I_ToxB isolate in these collections were equal to 59% and 52%, respectively. By using the Xfcp623 marker, the diagnostic product was amplified in winter cultivars ‘Bodry’, ‘Kavalerka’, ‘Timiryazevka 150’, ‘Shef’, ‘Anastasia’, ‘Barynya’, ‘Donskaya Step’, ‘Elanskaya’ and spring cultivars ‘Odeta’, ‘Stolypinskaya 2’, ‘Iren’ 2’ and ‘OMGAU 100’. All these cultivars were moderately susceptible to the isolate I_ToxA, with the exception of ‘Odeta’ and ‘Iren’ 2’, which may indicate a decrease in the expression level of the ToxA gene in genotypes of these cultivars.